Design and Manufacture of Portable Screw Turbine of Pico Hydro Power Plant for Road Lighting in Rural Area - Nofriadi Nofriadi; Azridjal Aziz; Rahmat Iman Mainil (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2023)
This study aims to design and manufacture a portable screw turbine of pico hydro power plant for road lighting in rural area. The portable screw turbine has the specifications of a turbine diameter of 23 cm, length of 1 m, number of threads of 5, shaft diameter of 6 cm and pitch of 22 cm. This screw turbine was tested by varying several turbine tilts angles, namely 15°, 30°, 45° and 60° with a flow rate used of 0.0054 m3/s. In field test was carried out at an angle of 30° with a flow rate of 0.125 m3/s. The test results show the angle of inclination of turbine affects the mechanical performance. Testing the 45° angle produced a mechanical power of 18.857 Watts with an efficiency of 35.669%. In the field testing was produced a generator power of 4 Watts. This screw turbine is expected to be another alternative as a pico-hydro scale power plant.